Peran Guru dalam Membantu Ketuntasan Belajar Peserta Didik dalam Pembelajaran Al-Qur'an Hadist di Mts Ma'arif Daarus Sa'adah Tahun Pelajaran 2016-2017: PERAN GURU DALAM MEMBANTU KETUNTASAN BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN AL QUR'AN – HADIS DI MTS AL MA'ARIF DAARUS SA'ADAH TAHUN PELAJARAN 2016 – 2017 - Ahmad Natsir Fitriopno (LPPM IAI Hasanuddin Pare-Kediri, 2017)
One of among the issues large in the education sector in indonesia is learning achievements the low average, another problem in the field of education in indonesia which talk about is that learning approach are still too dominated the role of teachers teacher centered teachers have more put students as an object and not as the subject of primary school students. Less well as provide opportunities for our education of students in a wide range of subjects, to develop the ability of holistic comfrehensif reflect, creative, objective and logical, have not use quantum learning as one of pulling in learning paradigm, and little regard for learning. The kind of research it uses the qualitative study, namely the approach of research that yields diskriptif data data in the form of written or spoken of other people and of observable behavior, namely associated in science that is run to obtain patiently factors and principles, careful and systematic manner to embody some the truth. Of the source of data in this research was the individuals concerned nature ketuntasan learn school tuition, either directly or indirectly.To get data accurate in research it is used a number of techniques data collection following; (1) the technique of observation, which as systematic observation or recording with the facts under investigation.This method applied in order to observe the facts is in a class teaching and learning during the foundation of the son of an and hadith, in this case related to ketuntasan strategy learning school tuition. The technique of the objective of the interview that is used: (a) in depth interviews, this means that group of researchers from ask you a few questions in depth from four to that deals with a focus on problems that had occurred; ( b ) interview open , of bond issuance will be the subject matter of the know understand and realize that when the two of them were interviewed and he knows what is got into the interview did. While the technique of documentation that is used to search for data that is concerned with research are now the subject of the bni share issuance namely; learners of learning achievements flyweight title on a unanimous, data on participants in primary school students who is undergoing a also held try program, syllabus and rpp the qur an easy as if they were ascending, of data concerning hal-hal pertaining to areas devastated by the may be researched pt pgn promised to supply the geographical area of, the vision and mission of, the state of teachers, the organizational structure of their discerning men will vanish or MTS al Madaaruss Sa adah, academic calendar they must, and the thing that is to another as related by the profile of the place of research.